An Intervention-Related Comparison of Preschoolers' Scores on the TGMD-2 and TGMD-3. Issue 4 (August 2021) - Palmer, Kara K.; Chinn, Katherine M.; Scott-Andrews, Katherine Q.; Robinson, Leah E.
This study compared preschoolers' fundamental motor skills (FMS) on the Test of Gross Motor Development 2nd and 3rd editions (TGMD-2 and TGMD-3) before (pretest) and after (posttest) a motor skill intervention. This study also compared FMS changes (TGMD raw and percentile scores for total score, and locomotor and object control/ball subscales) across the intervention when FMS were measured using the two editions. Sixty-four preschoolers ( Mage  = 4.4, SD  = 0.44 years) completed the TGMD-2 and TGMD-3 before and after a motor skill intervention. We determined the level of agreement between assessments using intra-class correlations (ICC), Lin's Concordance Correlation Coefficient, and Bland-Altman plots. Overall, our results support an acceptable relative agreement between the TGMD-2 and TGMD-3 for raw scores, but there were variable strengths of agreement (by subscales) for percentile scores. Both assessments supported the efficacy of the intervention. This consistent demonstration of efficacy but varied strength of agreement suggests that the TGMD-2 and TGMD-3 are similar but not interchangeable.